Pengaruh Kualitas Produk Dan Citra Merek Terhadap Loyalitas Pelanggan Produk Maybelline Pada Industri Kosmetik Di Jakarta Pusat - Angelica Ripassa; Indra Sumarna Sobari (JAMBIS : Jurnal Administrasi Bisnis, 2025)
This research aims to examine the Impact of Product Quality and Brand Image on Customer Loyaltytoward Maybelline products in Central Jakarta. The research method employed is non-probabilitysampling, specifically using convenience/accidental sampling, with a total of 100 respondents. The datawere collected through questionnaires distributed to respondents via social media using Google Forms.Instrument testing was conducted using validity and reliability tests. Data analysis involved classicalassumption tests, multiple linear regression analysis, t-tests, f tests, and the coefficient ofdetermination. The findings indicate that product quality has a positive and significant effect oncustomer loyalty to Maybelline products in Central Jakarta. Likewise, brand image also has a positiveand significant effect on customer loyalty. Furthermore, product quality and brand image simultaneouslyhave a positive and significant influence on customer loyalty toward Maybelline products in CentralJakarta.Keywords: Product Quality, Brand Image, Customer Loyalty